2017
DOI: 10.1177/1933719116681515
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Endometrial Expression of Leukemia Inhibitory Factor Receptor Disrupts the STAT3 Signaling in Adenomyosis During the Implantation Window

Abstract: Significant reduction in LIFR expression and the reduced activation of subsequent signaling strongly suggest a working model of how the implantation markers, LIF, may affect the endometrium of patients with adenomyosis. These molecular changes supported the declined implantation rates reported in patients with adenomyosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 55 publications
0
31
2
Order By: Relevance
“…Immunohistochemistry was performed on placental sections as previously described (27) using the primary antibody (rabbit anti-LIN28B, 40 mg/ml, ab71415, RRID:AB_2135050; Abcam, Cambridge, United Kingdom) and detected using a biotinylated goat anti-rabbit secondary antibody (BA-1000, RRID:AB _2313606; Vector Laboratories, Burlingame, CA, USA) together with the avidin-biotin-peroxidase complex (Vectastain ABC Kit, pk6200, RRID:AB_2336826; Vector Laboratories) followed by 3,39diaminobezidine (sk-4100, RRID:AB_2336382; Vector Laboratories) incubation as a substrate and counterstained with hematoxylin (H3404, RRID:AB_2336843; Vector Laboratories).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Immunohistochemistry was performed on placental sections as previously described (27) using the primary antibody (rabbit anti-LIN28B, 40 mg/ml, ab71415, RRID:AB_2135050; Abcam, Cambridge, United Kingdom) and detected using a biotinylated goat anti-rabbit secondary antibody (BA-1000, RRID:AB _2313606; Vector Laboratories, Burlingame, CA, USA) together with the avidin-biotin-peroxidase complex (Vectastain ABC Kit, pk6200, RRID:AB_2336826; Vector Laboratories) followed by 3,39diaminobezidine (sk-4100, RRID:AB_2336382; Vector Laboratories) incubation as a substrate and counterstained with hematoxylin (H3404, RRID:AB_2336843; Vector Laboratories).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Adenomyosis is a common and chronic gynaecological disease that affects 10%‐80% of women of reproductive age worldwide . It is characterized by the presence of endometrial stroma and glands within the myometrium and its main clinical features include chronic pelvic pain, abnormal uterine bleeding, menorrhagia, dysmenorrhea, dyspareunia and infertility . In recent years, due to the advancement of imaging techniques such as transvaginal ultrasound scan (TVUS) and magnetic resonance imaging (MRI), substantial evidences suggest that adenomyosis may develop more often among younger women .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It is characterized by the presence of endometrial stroma and glands within the myometrium and its main clinical features include chronic pelvic pain, abnormal uterine bleeding, menorrhagia, dysmenorrhea, dyspareunia and infertility. 1,[3][4][5] In recent years, due to the advancement of imaging techniques such as transvaginal ultrasound scan (TVUS) and magnetic resonance imaging (MRI), substantial evidences suggest that adenomyosis may develop more often among younger women. 6,7 To date, no novel compound is reported to develop for adenomyosis and clinical studies on the well-conducted pharmacologic treatment are seldom reported.…”
Section: Introductionmentioning
confidence: 99%
“…In the endometrium, LIF and LIFR expression are particularly prominent in the secretory phase of the menstrual cycle, indicating a potential role in embryo implantation . Indeed, expression of LIFR, LIF, and its coreceptor gp130 is reduced in subfertile endometriosis patients compared with healthy controls, and a reduction of LIFR expression is associated with reduced downstream signaling via signal transducer and activator of transcription 3 in women with adenomyosis during the window of implantation . Therefore, although GSI‐induced inhibition of LIFR expression can be expected to aid in targeting stem cell properties in endometriotic lesions, it may cause unwanted fertility‐related side effects.…”
Section: Discussionmentioning
confidence: 99%